Evaluation of effervescent floating matrix tablet formulations of salbutamol sulfate using full factorial design - Rao, Monica RP; Sonar, Girish S; Mandsaurwale, Rachana R; Vanshiv, Swapnila D (Asian Journal of Pharmaceutics (AJP), 2014)
The purpose of this research was to formulate and optimize an effervescent floating tablet formulation of salbutamol sulfate using full factorial design. Salbutamol sulfate has an absorption window in the stomach and in the upper part of the small intestine. A 32 full factorial design (eight runs) was utilized to optimize the formulation wherein the content of hydroxylpropyl methyl cellulose (HPMC) (X1) and sodium bicarbonate (X2) were taken as independent variables and % drug release after 6 h (Y1), t50% (Y2), and buoyancy lag time (BLT) (Y3) were taken as the dependent variables. Salbutamol sufate, HPMC K4M and HPMC K100M CR, stearic acid, talc, dicalcium phosphate, polyvinyl pyrrolidone, and magnesium stearate were used for the current research work. Two viscosity grades of HPMC as matrix materials were used for formulating the tablets, which were prepared by wet granulation. The release data were evaluated by the model-dependent (curve fitting) method using the PCP Disso v2.08 software. Optimization studies were carried out using the Design Expert Software (Version 7.0.3). The in vitro drug release mechanism showed anomalous transport. An increase in the concentration and viscosity grade of the polymer resulted in a decrease in the release rate, but it was found that at a higher concentration of HPMC, the viscosity grade did not significantly affect the drug release. Concentration of both HPMC and sodium bicarbonate had a significant effect on the BLT. Optimized effervescent floating tablets of salbutamol sulfate were successfully prepared and a good correlation was observed between predicted and actual values of the dependent variables chosen for the study. Viscosity grade of HPMC did not significantly impact the floatability of the dosage form. Thus, we can conclude that a combination of HPMC, stearic acid, and sodium bicarbonate can be used to increase the gastric residence time of the dosage form up to 12 h.